Allison Shaw: capstone - Shaw, Allison, artist (Colorado State University. Libraries, 2015)
The artist's statement: It is said that "a picture is worth a thousand words", however, the quantity of words a graphic designer needs is often no more than a few. Within design and form, we create impact. Shapes, colors, and texture are all elements used to evoke a response. The impact and response that comes from art is what pushes me to pursue graphic design, the art of visual communication. The body of work I have created over the course of my college career helped me discover how I can say a lot, with only a little. I embrace the simple shapes and explore the innovative solutions they possess. A shape as simple as a circle communicates unity and endurance. A square represents balance and stability. A visual identity gives clients a voice and an opportunity to say much with little. My passion is to help people. Whether it is simply holding a door open or volunteering for a good cause, I want to use my abilities toward the good of the people. My abilities in graphic design are no exception. As I continue with graphic design, I aspire to help even more people who are in need of a creative eye and create an impact worth a thousand words.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design